Pengaruh Antara Kepemimpinan Kepala Sekolah, Kinerja Guru dan Layanan Administrasi Terhadap Efektivitas Pengelolaan Sekolah di MTs Yasti 1 Kabupaten Sukabumi - Ida Farida; Endin Nasrudin; Siti Qomariyah; Yurna Bachtiar; Nadzifah Fiddiana (LP. Ma'arif Janggan Magetan, 2022)
There are so many ineffective school managements. This is due to ineffective head leadership, poor teacher performance or less organized administrative services. Therefore, it is necessary to know the relationship between the principal's leadership, teacher performance and administrative services to the effectiveness of school management. This study aims to determine the relationship between principal leadership, teacher performance and administrative services to the effectiveness of school management. The sample of this study was 50 teachers. Sampling for principals and administrative employees using stratified random disproportionate techniques and sampling for teachers using purposive sampling techniques. This research uses quantitative methods with measuring instruments in the form of questionnaires. Data analysis was performed with a multivariate correlation test (double correlation). The results obtained in this study show a relationship between the principal's leadership, teacher performance, and administrative services to the effectiveness of schools in MTs. Yasti 1 Sukabumi District